2015
DOI: 10.1002/jso.24008
|View full text |Cite
|
Sign up to set email alerts
|

Robotic surgery for early stage cervical cancer: Evolution and current trends

Abstract: The management of early stage cervical cancer often includes surgery in the form of radical hysterectomy, radical trachelectomy, or radical parametrectomy. Surgical techniques have evolved to include minimal invasive approaches, and more recently, to include robotic assisted techniques. This review highlights the evolution of surgical management of early cervical cancer and specifically explores robotic assisted radical hysterectomy, radical trachelectomy, radical parametrectomy, and the role of neoadjuvant ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 102 publications
0
10
0
Order By: Relevance
“…The information on outcomes is limited to cases with common cervical carcinoma histology. Radical trachelectomy (RT), a valid alternative to radical hysterectomy, can be performed vaginally, abdominally, or endoscopically in patients with FIGO stage IA−IB cervical cancer (lesion ≤2 cm without extension to internal os/low segment) who want to preserve fertility [ 16 18 ]. The abdominal route is optimal when vaginal access is not possible in nulligravida women, as it allows surgeons to obtain more parametrium than that via the vaginal route.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The information on outcomes is limited to cases with common cervical carcinoma histology. Radical trachelectomy (RT), a valid alternative to radical hysterectomy, can be performed vaginally, abdominally, or endoscopically in patients with FIGO stage IA−IB cervical cancer (lesion ≤2 cm without extension to internal os/low segment) who want to preserve fertility [ 16 18 ]. The abdominal route is optimal when vaginal access is not possible in nulligravida women, as it allows surgeons to obtain more parametrium than that via the vaginal route.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 9% of patients had cervical stenosis [ 8 , 17 ], and the recurrence rate after ART was 0–4.8%, while the pregnancy rate after ART was 15.5–44% [ 7 , 8 ]. The safety and feasibility of laparoscopic and robotic RT have been documented [ 18 ]. Compared with ART, laparoscopic and robotic approaches result in less blood loss, shorter hospital stays, comparable cancer recurrence rates, and similar operative outcomes [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…[5,6] An increasing number of studies have reported the benefits of robotic radical hysterectomy (RRH) including better ergonomics, higher definition, the ability to see in 3-dimensionals, 7° of wrist-like motion, tremor filtering, motion scaling, and less fatigue. [7]…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that robot-assisted laparoscopic surgery can provide value in many surgical applications (e.g., gynecologic, 1 liver, 2 and rectal 3 surgery), it is still most commonly used for the surgical management of prostate cancer. 4 In addition to the removal of the primary prostate cancer (prostatectomy), such procedures are often accompanied by a form of lymph node dissection focused on the removal of lymphatic metastases, e.g., a (extended) lymphadenectomy, a sentinel node (SN) procedure, 5 or, in the future, a prostate-specific membrane antigentargeted nodal dissection.…”
Section: Introductionmentioning
confidence: 99%